Estruturas e vocabulário no 4.º ano primário italiano e português : comparação de histórias orais e escritas na duas línguas - Girolami-Boulinier, Andrée, 1913-1998 (1991)
The autors first analysed the syntax and vocabulary of 240 stories told by Italian and Portuguese fourth-year primary school children and went on to establish a «dictionary» of the lexical words which are used in these stories by the Italian and Portuguese pupils.